White paper on guidelines concerning enteric nervous system stem cell therapy for enteric neuropathies - Burns, Alan J.; Schäfer, Karl Herbert (Developmental biology, 2016)
Over the last 20 years, there has been increasing focus on the development of novel stem cell based therapies for the treatment of disorders and diseases affecting the enteric nervous system (ENS) of the gastrointestinal tract (so-called enteric neuropathies). Here, the idea is that ENS progenitor/stem cells could be transplanted into the gut wall to replace the damaged or absent neurons and glia of the ENS. This White Paper sets out experts’ views on the commonly used methods and approaches to identify, isolate, purify, expand and optimize ENS stem cells, transplant them into the bowel, and assess transplant success, including restoration of gut function. We also highlight obstacles that must be overcome in order to progress from successful preclinical studies in animal models to ENS stem cell therapies in the clinic.